Refine the decision cycle model of interaction in design multimedia interface to support for learner control - Ngô Anh Tuấn (Journal of Technical Education Science, 2012)
Multimedia technology offers instructional designers an unprecedented opportunity to create richly interactive learning environments. With greater design freedom comes complexity. The standard answer to the problems of too much choice, disorientation, and complex navigation is thought to lie in the way we design the interactivity in a system. Unfortunately, the theory of interactivity is at an early stage of development. After critiquing the decision cycle model of interaction – the received theory in human computer interaction – This paper presents arguments to show that humans have several ways of interacting with their environments which resist accommodation in the decision cycle model. These additional ways of interacting include: preparing the environment, maintaining the environment, and reshaping the cognitive congeniality of the environment. Understanding how these actions simplify the computational complexity of our mental processes is the first step in designing the right sort of resources and scaffolding necessary for tractable learner controlled learning environments.